Self-lubricating composite coating on air foil bearing shaft by Hollow Cathode Plasma Jet - Yang, MK; Yang, HS; Park, JK; Ryu, K; Lee, YB; Lee, JK (TRANS TECH PUBLICATIONS LTD, 2005)
The self-lubricating composite films were deposited on Inconel 718 by Hollow Cathode Plasma Jet (HCPJ). These composite materials consist of chrome nickel alloy matrix and Ag, BaF2/CaF2 solid lubricants. The Cr2O3-NiCr-Ag composite thin film was crystallized and had the main peaks of Cr2O3 (012) and Ag (111). The deposition rate of 200 nm/min by HCPJ was much faster than the ordinary R.F. planar magnetron sputtering. The surface roughness of coated shaft was 30 nm.
Keywords: FILMS